2016
DOI: 10.1128/mcb.00956-15
|View full text |Cite
|
Sign up to set email alerts
|

Shp2 Associates with and Enhances Nephrin Tyrosine Phosphorylation and Is Necessary for Foot Process Spreading in Mouse Models of Podocyte Injury

Abstract: bIn most forms of glomerular diseases, loss of size selectivity by the kidney filtration barrier is associated with changes in the morphology of podocytes. The kidney filtration barrier is comprised of the endothelial lining, the glomerular basement membrane, and the podocyte intercellular junction, or slit diaphragm. The cell adhesion proteins nephrin and neph1 localize to the slit diaphragm and transduce signals in a Src family kinase Fyn-mediated tyrosine phosphorylation-dependent manner. Studies in cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 68 publications
(119 reference statements)
2
60
0
Order By: Relevance
“…Functional integrity of the glomerular filter cannot be assessed with the protamine sulfate model of podocyte injury, as the animals are sacrificed following the experiment. SHP-2-deleted mouse podocytes subjected to the nephrotoxic serum demonstrated that proteinuria is reduced in addition to the absence of foot process effacement [25]. Similar observations have been made when focal adhesion regulatory proteins, such as focal adhesion kinase (FAK), Crk, and uPAR, are deleted in the mouse [24,36,37].…”
Section: The Podocyte Effacement Processsupporting
confidence: 62%
See 4 more Smart Citations
“…Functional integrity of the glomerular filter cannot be assessed with the protamine sulfate model of podocyte injury, as the animals are sacrificed following the experiment. SHP-2-deleted mouse podocytes subjected to the nephrotoxic serum demonstrated that proteinuria is reduced in addition to the absence of foot process effacement [25]. Similar observations have been made when focal adhesion regulatory proteins, such as focal adhesion kinase (FAK), Crk, and uPAR, are deleted in the mouse [24,36,37].…”
Section: The Podocyte Effacement Processsupporting
confidence: 62%
“…Both are seen markedly less in FSGS compared with membranous nephropathy and minimal change disease, suggesting that there may be important differences in their signaling processes [24]. Lower levels of phospho-SHP-2 staining were observed in the glomerulus from biopsy samples from FSGS patients compared with those from patients with membranous and minimal change disease [25]. The discrepancy could be explained by a decrease in the number of podocytes in FSGS at the time of biopsy; alternatively, there could be distinct signaling pathways involved in the different proteinuric glomerular diseases.…”
Section: Podocyte: Links To Glomerular Basement Membranementioning
confidence: 92%
See 3 more Smart Citations